PENINGKATAN PENGETAHUAN IBU-IBU PEMBINAAN KESEJAHTERAAN KELUARGA DASA WISMA KALONGAN KULON, TASIKMADU TENTANG CEMARAN BAKTERI PADA SAUS SIOMAI - Dewi Arini, Liss Dyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
Mother is a leader figure in a family who is in charge of managing family healthy food needs. The knowledge about hygienic food for the Family Welfare Coaching Mothers at Dasa Wisma Kalongan Kulon, Tasikmadu is still limited, because many of them come from poor families and have less educational background so that the basic knowledge of the family is not maximal (less attention). This community service activity aims to improve understanding of family welfare coaching mothers to know healthy and hygienic food, to improve understanding of family welfare coaching mothers about healthy and hygienic food characteristics and to improve awareness to society not to buy food at random. The method of counseling is done by lecturing method and explanation about healthy and hygienic food and contamination or contamination of bacteria in siomai sauce from peddlers with media poster and power point. The results of community service activities are family welfare coaching mothers understand about healthy and hygienic food and food contaminated or contaminated with bacteria, especially in siomai sauce. The conclusion of this community service activity is family welfare coaching mothers can know the benefits of healthy and hygienic food for body and family welfare coaching mothers are aware to be more careful in buying food outside so that family health, especially on school children is more secure and family welfare coaching mothers understood how to choose healthy and hygienic food for her family.Keywords: Family Welfare Coaching Mothers, health, hygienic, sauce of siomai